2019
DOI: 10.1038/s41598-019-52390-4
|View full text |Cite
|
Sign up to set email alerts
|

Method and its Composition for encapsulation, stabilization, and delivery of siRNA in Anionic polymeric nanoplex: An In vitro- In vivo Assessment

Abstract: Small interfering RNA (siRNA) are synthetic RNA duplex designed to specifically knockdown the abnormal gene to treat a disease at cellular and molecular levels. In spite of their high potency, specificity, and therapeutic potential, the full-fledged utility of siRNA is predominantly limited to in vitro set-up. Till date, Onpattro is the only USFDA approved siRNA therapeutics available in the clinic. The lack of a reliable in vivo siRNA delivery carrier remains a foremost obstacle towards the clinical translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…The ODA-based lipoplex (F4) was prepared at different (N/P) atomic ratios that were tested: 1, 2, 4, 6, 8 and 10, keeping the siRNA quantity constant at 1000 pmol. The lipid nanoparticle size and charge were observed using a Zetasizer Nano ZS (Malvern Instruments, Malvern, UK) [45].…”
Section: Determination Of Optimal Lipid-to-sirna Complexation Ratio F...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ODA-based lipoplex (F4) was prepared at different (N/P) atomic ratios that were tested: 1, 2, 4, 6, 8 and 10, keeping the siRNA quantity constant at 1000 pmol. The lipid nanoparticle size and charge were observed using a Zetasizer Nano ZS (Malvern Instruments, Malvern, UK) [45].…”
Section: Determination Of Optimal Lipid-to-sirna Complexation Ratio F...mentioning
confidence: 99%
“…The obtained pellets were re-suspended in PBS and acidic solutions (3 mL). Further, the pellets were stirred at 100 rpm for 7 days at 37 • C. At different time points, the samples were aliquoted and were centrifuged at 13,000× g for 28 min at 25 • C [45]. The collected supernatant with an equal volume of fresh PBS or acidic solution was added to the sample.…”
Section: In Vitro Release Studiesmentioning
confidence: 99%
“…The anionic surface charge of UCVs maintains its vascular retention for a longer period. [ 3,31 ] The prepared ultrasound contrast vesicles exhibited 70% equivalent gray‐scale ultrasound contrast as compared to SonoVue (Figure 2a). It was observed that DPPC/PEG40S (95:5) formed a foamy suspension due to immiscibility of amphiphilic PEG40S in lipid dispersion after the agitation process.…”
Section: Resultsmentioning
confidence: 99%
“…This given dose to the animal was determined through the confirmation of encapsulation of siRNA as per the protocol reported by Cun and Raval with slight modifications [36,37]. For the %EE determination, accurately weighed (5.0 mg) lyophilized particles matrix were solubilized in 100 µL of chloroform (for SC shell) with 400 µL of aqueous TE buffer (for SPC core).…”
Section: Animalsmentioning
confidence: 99%